2006
DOI: 10.1002/jctb.1490
|View full text |Cite
|
Sign up to set email alerts
|

Ozonation of weathered olive mill wastewaters

Abstract: The treatment of fully and partly weathered olive mill wastewaters by means of ozonation was investigated, with emphasis on the effect of treatment conditions (organic loading, treatment time, ozone concentration) on the extent of chemical oxygen demand (COD) and total phenol degradation, colour removal as well as ecotoxicity to the marine bacterium Vibrio fischeri. In general, ozonation was capable of substantially reducing the concentration of phenols as well as decolourising the effluent after relatively sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 10 publications
1
24
0
Order By: Relevance
“…7,8 Ozonation processes result in the cleavage of unsaturated bonds and formation of lower molecular weight compounds which are more readily biodegradable. 9,10 Ozonation as an effective method has been applied to treat HAs for years due to its capability of minimizing the formation of trihalomethanes that are known to have carcinogenic effects. 11 -13 By using characterization methods, it was demonstrated that ozonation of HAs leads to decoloration and to decrease in UV absorbance due to the cleavage of chromophores, 14 -17 as can be seen in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Ozonation processes result in the cleavage of unsaturated bonds and formation of lower molecular weight compounds which are more readily biodegradable. 9,10 Ozonation as an effective method has been applied to treat HAs for years due to its capability of minimizing the formation of trihalomethanes that are known to have carcinogenic effects. 11 -13 By using characterization methods, it was demonstrated that ozonation of HAs leads to decoloration and to decrease in UV absorbance due to the cleavage of chromophores, 14 -17 as can be seen in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…These results were in agreement with Fiorentino et al (2003) who concluded that several individual phenolic compounds had a strong toxic potential on different trophic levels in the aquatic system, evaluating the OMW toxicity on four organisms: the algae P. subcapitata, the rotifer Brachionus calyciflorus, and two crustaceans, the cladoceran D. magna and the anostracan T. platyurus. Karageorgos et al (2006) also observed that in most of their experiments the toxicity values decrease with the decrease of organic content, but an increase of residual phytoxicity was observed possibly due to the production of short-chain fatty acids (C8-C9) during the oxidative process of ozonation.…”
Section: Physico-chemical Processesmentioning
confidence: 90%
“…The most usual way to manage these wastewaters consists in dumping them in evaporation pounds (Karageorgos et al 2006), which are an environmental danger for groundwater besides the production of bad smells (Azbar et al 2004). Moreover, this process depends upon the weather conditions.…”
Section: Single Ozonationmentioning
confidence: 99%
“…It means that the effluent may not evaporate by the end of the summer and the pond may not be available in the next year. Karageorgos et al (2006) analyzed this possibility and investigated the potential of ozonation on the management of such weathered effluents (Table 1). Ozone was able to remove up to 80% of phenolic content (TPh) and color in 120 min of reaction.…”
Section: Single Ozonationmentioning
confidence: 99%